Upaya Meningkatkan Motivasi Belajar Matematika Melalui Penggunaan Media Kartu Angka pada Siswa Kelas III SDN 213/II Lubuk Beringin - Asad, Muhammad (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to improve the mathematics learning motivation of third-grade students at SDN 213/II Lubuk Beringin through the use of number card media. This research is a Classroom Action Research (CAR) conducted in two cycles.